Quantitative Proteomics of an Amphibian Pathogen, Batrachochytrium dendrobatidis, following Exposure to Thyroid Hormone - Thekkiniath, Jose (PLoS One, 2015)
Batrachochytrium dendrobatidis (Bd), a chytrid fungus, has increasingly been implicated as a major factor in the worldwide decline of amphibian populations. The fungus causes chytridiomycosis in susceptible species leading to massive die-offs of adult amphibians. Although Bd infects the keratinized mouthparts of tadpoles and negatively affects foraging behavior, these infections are non-lethal. An important morphogen controlling amphibian metamorphosis is thyroid hormone (T(3)). Tadpoles may be infected with Bd and the fungus may be exposed to T(3) during metamorphosis. We hypothesize that exposure of Bd to T(3) may induce the expression of factors associated with host colonization and pathogenicity. We utilized a proteomics approach to better understand the dynamics of the Bd-T(3) interaction. Using liquid chromatography-mass spectrometry (LC-MS), we generated a data set of a large number of cytoplasmic and membrane proteins following exposure of Bd to T(3). From these data, we identified a total of 263 proteins whose expression was significantly changed following T(3) exposure. We provide evidence for expression of an array of proteins that may play key roles in both genomic and non-genomic actions of T(3) in Bd. Additionally, our proteomics study shows an increase in several proteins including proteases and a class of uncommon crinkler and crinkler-like effector proteins suggesting their importance in Bd pathogenicity as well as those involved in metabolism and energy transfer, protein fate, transport and stress responses. This approach provides insights into the mechanistic basis of the Bd-amphibian interaction following T(3) exposure.